The analysis of directive function in the fifty shades freed novel - Dewi, Ni Komang Chandra; Juniartha, I Wayan; Karya, I Wayan Sidha (Institut Pariwisata dan Bisnis Internasional, 2020)
The aims of this research are to describe the types of directive illocutionary acts function in Fifty Shades Freed novel and to find out the types, which is mostly used in this novel. This is descriptive qualitative research. Observation was used in collecting the data. There were some steps in collecting the data: read the novel several times to understand the plot and examined the dialogue to distinguish the types of directive illocutionary act function found in the novel. The researcher applied Searle (1979) to analyze the data. The result of the research shows that there are 39 utterances containing directive illocutionary acts function. The data were classified into four; ordering (21), forbidding (1), requesting (4), suggesting (1), and asking (11). Of the total 39 directive illocutionary acts function, ordering are the most used type of directive illocutionary acts function because the character mostly expressed their utterances by ordering.